2013
DOI: 10.1007/s10858-013-9777-z
|View full text |Cite
|
Sign up to set email alerts
|

NMR spectroscopy reveals unexpected structural variation at the protein–protein interface in MHC class I molecules

Abstract: β2-Microglobulin (β2m) is a small, monomorphic protein non-covalently bound to the heavy chain (HC) in polymorphic major histocompatibility complex (MHC) class I molecules. Given the high evolutionary conservation of structural features of β2m in various MHC molecules as shown by X-ray crystallography, β2m is often considered as a mere scaffolding protein. Using nuclear magnetic resonance (NMR) spectroscopy, we investigate here whether β2m residues at the interface to the HC exhibit changes depending on HC pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 63 publications
3
29
0
Order By: Relevance
“…Given that binding of peptide and b 2 m to the heavy chain are cooperative Elliott et al, 1991), it is mechanistically consistent that the C84-C139 disulfide bond also increases the b 2 m binding affinity of K b . As we see no significant differences between wild-type K b and K b -Y84C in the crystal structure positions of the residues at the interface of the heavy chain with b 2 m (Shields et al, 1999;Achour et al, 2002;Achour et al, 2006;Hee et al, 2012), we propose that the coupling between peptide binding and b 2 m binding occurs through the conformational dynamics of the heavy chain Beerbaum et al, 2013;Bailey et al, 2014). Further investigation of K b -Y84C might elucidate this coupling, which is central to MHC-I stability and to the molecular understanding of cellular peptide selection.…”
Section: Discussionmentioning
confidence: 55%
“…Given that binding of peptide and b 2 m to the heavy chain are cooperative Elliott et al, 1991), it is mechanistically consistent that the C84-C139 disulfide bond also increases the b 2 m binding affinity of K b . As we see no significant differences between wild-type K b and K b -Y84C in the crystal structure positions of the residues at the interface of the heavy chain with b 2 m (Shields et al, 1999;Achour et al, 2002;Achour et al, 2006;Hee et al, 2012), we propose that the coupling between peptide binding and b 2 m binding occurs through the conformational dynamics of the heavy chain Beerbaum et al, 2013;Bailey et al, 2014). Further investigation of K b -Y84C might elucidate this coupling, which is central to MHC-I stability and to the molecular understanding of cellular peptide selection.…”
Section: Discussionmentioning
confidence: 55%
“…Thirdly, the differences in MHC I plasticity and corresponding selector function have been shown here for three HLA-B molecules, and the generality of this observation remains to be explored, in particular by considering additional HLA alleles and point mutations. However, there is in vitro and computational evidence suggesting that plasticity is a common functional property of MHC I192022244546 and many other proteins3647.…”
Section: Discussionmentioning
confidence: 99%
“…Another study also showed that β 2 m seems to sense allelic as well as peptide-induced conformational variations and accommodates to them, showing a high degree of plasticity within the inter-domain interface with the HC domains (110). NMR-chemical-shift changes of complexes were most pronounced in the region close to the F-pocket.…”
Section: Dynamic Features Of Peptide-bound Mhc Complexesmentioning
confidence: 99%